Student engagement and conceptual change through gamified flipped classrooms in biology education - Safarini, Melly; Fitriani, Salma; Suwandi, Tri; Rahmat, Adi (Universitas Negeri Jakarta, 2026)
The gamified flipped classroom (GFC) is an extension of the traditional flipped classroom (FC) that embeds gamification elements into digital independent learning prior to face-to-face sessions. This study addresses the limited student engagement and persistent misconceptions commonly found in ecosystem learning by comparing students’ cognitive engagement, conceptions, and conceptual change patterns when learning through FC and GFC. A quasi-experimental design was employed involving 70 tenth-grade students assigned to FC and GFC groups, with learning conducted over four meetings. Cognitive engagement was measured using the four-scale Student Course Cognitive Engagement Instrument (SCCEI) after the intervention, supported by semi-structured interviews and documentation of student learning notes. Students’ conceptions were assessed using a four-tier multiple-choice test administered before and after learning, and conceptual change patterns were examined based on shifts in conception categories from pretest to posttest. The data were analyzed descriptively. The results indicate that students who learned through GFC demonstrated higher cognitive engagement across all indicators, developed more scientifically accurate conceptions, and exhibited more positive conceptual change patterns than those who learned through FC. GFC was particularly effective in reducing misconceptions, increasing sound understanding, and promoting construction-type conceptual changes. These findings suggest that integrating gamification into flipped classroom learning can enhance cognitive engagement and support deeper reconstruction of students’ conception in biology education. It is recommended that GFC be considered as an alternative instructional strategy to improve concept mastery in ecosystem learning and to support more meaningful student engagement.